Effect of Berberine on Hyperuricemia and Kidney Injury: A Network Pharmacology Analysis and Experimental Validation in a Mouse Model - Li Q; Huang Z; Liu D; Zheng J; Xie J; Chen J; Zeng H; Su Z; Li Y (Dove Medical Press, 2021)
Qiaoping Li,1,* Ziwei Huang,2,* Defu Liu,3 Jingna Zheng,1 Jianhui Xie,4- 6 Jiannan Chen,1 Huifang Zeng,2 Ziren Su,1 Yucui Li1 1School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People's Republic of China; 2The First Affiliated Hospital of Chinese Medicine, Guangzhou University of Chinese Medicine, Guangzhou, 510405, People's Republic of China; 3School of Basic Medical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People's Republic of China; 4The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, 510120, People's Republic of China; 5State Key Laboratory of Dampness Syndrome of Chinese Medicine, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, 510120, People's Republic of China; 6Guangdong Provincial Key Laboratory of Clinical Research on Traditional Chinese Medicine Syndrome, Guangzhou, 510120, People's Republic of China*These authors contributed equally to this workCorrespondence: Yucui Li; Ziren SuGuangzhou University of Chinese Medicine, Guangzhou, 510006, People's Republic of ChinaTel +86 20 39358517Fax +86 20 39358390Email liyucui@gzucm.edu.cn; suziren@gzucm.edu.cnPurpose: Berberine (BBR) is an active component of Phellodendri Cortex (PC), which is a traditional Chinese medicine that has been prescribed clinically for hyperuricemia (HUA) for hundreds of years. Many studies reported the anti-inflammatory and nephroprotective properties of BBR and PC; however, the therapeutic effects of BBR on HUA have not been explored. This study aims to investigate the efficacy and mechanism of BBR for treating HUA.Methods: The mechanism of BBR in the treatment of HUA were predicted by network pharmacology. A mouse model of HUA established by potassium oxonate and hypoxanthine was used to verify the prediction. The levels of serum uric acid (UA), urea nitrogen (BUN) and creatinine (CRE) were determined by biochemical test kits. Hematoxylin and eosin staining of kidney tissues was used to observe the kidney damage. ELISA kits were applied to detect the levels of interleukin (IL)-1β and IL-18 in serum and kidney tissues. Quantitative real-time PCR and Western blotting were adopted to analyze the expression of NLRP3, ASC, Caspase1, IL-1β and URAT1. The expressions of URAT1 in the kidney tubules were visualized by immunohistochemical staining. Molecular docking was used to assess the interaction between URAT1 and BBR.Results: The network pharmacology screened out 82 genes and several inflammation-related signaling pathways related to the anti-hyperuricemia effect of BBR. In the in vivo experiment, BBR substantially decreased the level of UA, BUN and CRE, and alleviated the kidney damage in mice with HUA. BBR reduced IL-1β and IL-18, and downregulated expressions of NLRP3, ASC, Caspase1 and IL-1β. BBR also inhibited expression of URAT1 and exhibited strong affinity with this target in silico docking.Conclusion: BBR exerts anti-HUA and nephroprotective effects via inhibiting activation of NLRP3 inflammasome and correcting the aberrant expression of URAT1 in kidney. BBR might be a novel therapeutic agent for treating HUA.Keywords: berberine, hyperuricemia, URAT1, NLRP3 signaling pathway